PENERAPAN MODEL PEMBELAJARAN TIPE TGT (TEAMS GAMES TOURNAMENTS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF PADA SISWA SMK NEGERI 1 INDRALAYA UTARA (Jurnal Pendidikan Teknik Mesin, 2017)
This research is a classroom action research (PTK) using model Team GameTournamen on subjects Basic Works Automotive Engineering Class X TKR 3 SMK Negeri 1North Indralaya. Aiming fatherly increase the activity and student learning outcomes subjectsBasic Works Automotive Engineering Class X TKR 3 SMK Negeri 1 North Indralaya. Thesubjects were students of class X TKR 3 and the object of this study is a model Team GameTournamen. This research was carried out in three cycles consisting of three meetings. Based onthe results before the given action (T0) amounted to 40.55% with an average of 62.16, while aftera given action (T1) in the first cycle of 51.35% with an average of 64.86, whereas (T2) in cycleII amounted to 72.97% with an average of 73.24 and (T3) in the third cycle of 86.48% with anaverage of 80.54. As for the activity of students in the first cycle of 34.71%, in the second cycleof 52.59% and in the third cycle of 66.52%. Of the three cycles showed increased activity andstudent learning outcomes.